Trends in periodontal status and oral hygiene habits in Dutch adults between 1983 and 1995 - Kalsbeek H, Truin G-J, Poorterman JHG, van Rossum GMJM, van Rijkom HM, (Blackwell Synergy, 2000)
In 1995, a dental survey, similar to one carried out in 1983, was performed among persons aged 25–54 in the city of ’s-Hertogenbosch, the Nether- lands. Objective: To describe trends in adults periodontal health between 1983 Key words: adults; epidemiology; oral and 1995. Methods: The participants were interviewed at home and clinically exam- hygiene habits; periodontal status; secular trends ined in a dental van. Results: Average scores for plaque, calculus, bleeding after probing and number of buccal root surfaces exposed to the oral cavity were lower H. Kalsbeek, TNO Prevention and Health, P.O. Box 2215, 2301 CE Leiden, the in 1995 than in 1983.